If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y+6y-y=3
We move all terms to the left:
2y+6y-y-(3)=0
We add all the numbers together, and all the variables
7y-3=0
We move all terms containing y to the left, all other terms to the right
7y=3
y=3/7
y=3/7
| 4x²+19x-140=0 | | -1/4x2+3x+1=0 | | 25x2-10x+1=0 | | 8x2-9x+3=0 | | 5x2+25x=0 | | y-12=34 | | 7y=4y+5 | | -1x2+9=0 | | 4.6+x=8.9 | | 6x+4x-26=86 | | x-34=-3.2 | | x+1.8=-3.2 | | 1x2-81=0 | | 6x-24=86+4x | | 10x-13=5x-18 | | -x+16=-3x+4 | | 12x+3=5x+45 | | -3x-12=-x-32 | | 100x2=0 | | 7x+22=29 | | 2x-2=-2x-14 | | 14x-5+3x²=0 | | -8w+4(w+7)=32 | | 3x=80-2x | | (y+2)*4=64 | | 4(x-2)-3x=1.7 | | 5a+3=25 | | 6b+18=8b+6 | | 9x2X16=0 | | -8v-48=2(v-4) | | 9x2•16=0 | | -8v48=2(v-4) |